(untitled) (Research, Society and Development, 2025)
This study addressed the impact of carbohydrate consumption in the pre-workout period and its benefits, as well as improvements in performance and performance in anaerobic exercises. The objective of this study was to investigate the importance of carbohydrate consumption in the pre-workout context, seeking to understand the improvement of physical performance and performance in anaerobic training. A bibliographic review was carried out based on scientific articles focusing on the types of carbohydrates and their energetic influences on the improvement of performance in anaerobic exercises. The results showed that their consumption presented performance improvements, favoring the performance of practitioners. It is concluded that carbohydrate consumption in the pre-workout period has a positive effect on increasing performance during training, improving both strength and endurance and performance.